Recent progress in biobased synthetic textile fibers - Tian, Wei; Huang, Kunzhen; Zhu, Chengyan; Sun, Zeyu; Shao, Lingda; Hu, Manyu; Feng, Xuhuang (Frontiers in Materials, 2022)
The use of synthetic fibers in our daily life is growing continuously; however, the excessive dependence of these chemical fibers on petroleum-based chemicals will lead to large consumption of non-renewable resources. Due to the scarcity of oil resources, economic and environmental problems, dependence on a few oil-rich countries, and predicted depletion of these resources, there has been increasing interest in the search for renewable resources to develop textile materials. Therefore, research and development of renewable resources, i.e., biobased materials, to reduce the use of fossil fuels have become increasingly important. Biobased synthetic fiber has a low carbon footprint in the synthesis process because its raw materials are derived from biomass. In addition, most biobased synthetic fibers have excellent biodegradability, which can be composted and degraded in natural environments or by microorganisms with or without specific conditions. However, all biobased fibers cannot be proven to be biodegradable, so the development of biodegradability is an important driving force for the progress of research on biobased fibers. In the past, biobased fiber has been obtained, extracted or synthesized from food crops, which was soon replaced by nonfood crops. With the idea of environmental protection, sustainability and resource conservation, it has become necessary to make nonfood crops and food residues biobased raw materials to obtain biobased textile fibers and even to develop ideal biobased raw materials that are carbon negatives, such as moss and CO2. Besides, there is huge potential for these biobased textile fibers to be used for sustainable clothing and medical textiles due to their nontoxicity, skin friendliness, and antibacterial properties. This review paper summarizes the recent development and clarifies key concepts in this domain.